2022
DOI: 10.3389/fphar.2022.884213
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Analysis of CYP-GUIDES Data: Assessing the Prevalence and Impact of Drug-Gene Interactions in an Ethnically Diverse Cohort of Depressed Individuals

Abstract: Introduction: Minority groups are underrepresented in pharmacogenomics (PGx) research. Recent sub-analysis of CYP-GUIDES showed reduced length of stay (LOS) in depressed patients with CYP2D6 sub-functional status. Our primary objective was to determine whether PGx guided (G) versus standard treatment (S) influenced LOS among different race/ethnic groups. Secondary objectives included prevalence of drug-gene interactions (DGIs) and readmission rates (RAR).Methods: Retrospective sub-analysis of CYP-GUIDES data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…A study on patients with recurrent depression found that an SNP in CYP2D6 was associated with the efficacy of the antidepressant duloxetine [ 92 ]. The CYP2D6 genotype has also been shown to have a possible impact on the length of hospitalization and risk of hospitalization in patients with major depressive disorder, thereby increasing the disease and financial burden on patients [ 93 ]. Unfortunately, SSRIs are currently ineffective in 60-70% of patients [ 94 - 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study on patients with recurrent depression found that an SNP in CYP2D6 was associated with the efficacy of the antidepressant duloxetine [ 92 ]. The CYP2D6 genotype has also been shown to have a possible impact on the length of hospitalization and risk of hospitalization in patients with major depressive disorder, thereby increasing the disease and financial burden on patients [ 93 ]. Unfortunately, SSRIs are currently ineffective in 60-70% of patients [ 94 - 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…This allele is uncommon in individuals of European ancestry (0.1%) but is common among those of African ancestry (8.7-10.8%). The omission of this allele means that an individual with this variant could be assigned a metabolizer status discordant with their "true" status (e.g., assigned a normal metabolizer when, in fact, they are an intermediate metabolizer) [21], highlighting the importance of considering ancestry when ordering PGx testing [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…In their randomized controlled trial, Tortora et al (2020) compared the hospital length of stay (LOS) of an ethnically diverse group of patients with severe depressive disorders that were either given standard therapy (Group S) or genetically-guided therapy (Group G). For our first illustrative example, we followed the sub-analysis of Crutchley & Keuler (2022) in omitting all observations with LOS ≤ 3 days; and fit a logistic regression model for the question how does ethnicity affect the probability of staying hospitalized longer than the overall median LOS (6.625 days), controlling for the variables age, gender, and group assignment (G or S).…”
Section: Application To a Clinical Trialmentioning
confidence: 99%